The wrong family - Fisher, Tarryn (Toronto, Ontario, Canada : Graydon House, 2020)
An off-kilter narrator witnesses the slow unraveling of a couple's strained marriage that erupts in unexpected ways, in a chilling tale of domestic suspense.
"Published by arrangement with Harlequin Books S.A."--Copyright page.
Includes reader's guide with discussion questions, author Q&A, and an excerpt from: The wives.
Keywords: Dysfunctional families -- Fiction; Family secrets -- Fiction; Domestic fiction; Psychological fiction; Thrillers (Fiction)